Gestió universitària i estils discursius - Cros, Anna; Bassols, Margarida; Álvarez, Ibis; Monereo, Carles; Sala, Guillem (Caplletra. Revista Internacional de Filologia, 2008)
This article presents some of the results from a broader research study of management styles within the Catalan university world. Two management styles are defined (the collegial and the managerial) and a relationship is established between some of the characteristics of these styles, some discursive features and the gender of the managers. Specifically, an analysis is made of the linguistic markers pertaining to the deictic modality in the discourse that constructs the identity of the analysed individuals. The markers of the deictic modality also make it possible to identity certain characteristic traits of men and women.Methodologically speaking, it could be said that the analysis of theindicators of a deictic-type discourse, and its linguistic markers, is a highly productive resource when it comes to evaluating the construction of the managers’ selfrepresentation and, therefore, of the way they see themselves in this role.